The impact of electronic device use on learning quality in young children: the mediating role of executive function and the moderating role of parental mediation - Qu, Fangbing; He, Shiqi; Yu, Feifei; Gu, Changwei (Frontiers in Public Health, 2025)
The increasing use of screen-based electronic devices among young children raises concerns about their potential impact on learning quality. While moderate and guided digital media use may support cognitive engagement, excessive or unregulated use can impair executive function and reduce learning outcomes. Parental mediation may serve as a protective factor, but its specific moderating role remains unclear. This study examined the relationship between electronic device use and learning quality in preschool children, focusing on the indirect pathway through executive function and the moderating role of parental mediation. A total of 3,322 preschool children (aged 3–5 years) participated, with their parents/guardians completed the questionnaires including Electronic Device Use, Learning Quality Parent Evaluation Scale, Executive Function Behavior Rating Scale, and Parental Mediation Questionnaire. Results showed that electronic device use negatively predicted executive function, which in turn negatively predicted children’s learning quality. Parental mediation moderated the indirect pathway, with higher levels of mediation attenuating the negative impact. These findings suggest that while excessive device use risks cognitive development, active parental mediation can mitigate adverse effects, highlighting the need for family-centered interventions.